Identification of risk factors for diabetes in Chinese middle-aged and elderly adults - Shuzhen Ma; Qianqian Sun; Yanqi Xu; Qiang Tu; Simao Xu (Scientific Reports)
Abstract This study aimed to identify and analyze the factors associated with the prevalence of diabetes among Chinese adults, using data from the China Health and Retirement Longitudinal Study (CHARLS). Data from the CHARLS cohort, with a mean age of 63.3 years, were analyzed using SPSS software. Descriptive statistics were performed for the overall population, as well as urban and rural subgroups. Logistic regression models were employed to assess the association between diabetes and variables such as age, gender, smoking, alcohol consumption, hypertension, and mental health disorders. Paired-sample t-tests were conducted to evaluate changes in diabetes prevalence across 2015, 2018, and 2020. The average of diabetes increased from 1.08 in 2015 to 1.15 in 2020, with a statistically significant difference (P < 0.001). Paired-sample t-tests showed significant differences between 2020 and 2018, as well as between 2018 and 2015 (P < 0.001). Logistic regression analysis identified hypertension (aOR = 0.447, 95% CI: 0.410–0.488, P < 0.001) and chronic disease (aOR = 0.024, 95% CI: 0.013–0.042, P < 0.001) as key risk factors for diabetes. Mild physical exercise was a protective factor (aOR = 0.813, 95% CI: 0.708–0.935, P < 0.01), while smoking (aOR = 1.220, 95% CI: 1.088–1.369, P < 0.001) and alcohol consumption (aOR = 1.125, 95% CI: 1.020–1.242, P < 0.05) increased the risk. Smoking and alcohol had a greater impact in urban areas, while hypertension and mental health disorders were more influential in rural areas. This study demonstrates that age, gender, smoking, alcohol consumption, hypertension, and mental disorders significantly influence the risk of diabetes among Chinese adults aged 45 and above. Distinct risk factors were identified between urban and rural populations, highlighting the necessity for tailored intervention strategies. The longitudinal analysis from 2015 to 2020 revealed a substantial increase in diabetes prevalence, underscoring the critical need for sustained and targeted public health efforts.